2022
DOI: 10.1590/1678-4324-2022210246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Incubation Time and “Browning” on Yield and Proximate Composition of the Edible Mushroom Lentinula edodes

Abstract: Lentinula edodes is the most consumed mushroom in the world, being cultivated mainly on waste coming from the forest industry. During shiitake cultivation, incubation is essential and is usually longer than in other edible mushrooms. This stage includes "browning", which is a process induced by exposure to a photoperiod and although it is believed to bring certain advantages to shiitake cultivation, it has not been widely studied. In this work, we evaluated how the incubation time, the use of different strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(37 reference statements)
0
0
0
Order By: Relevance
“…Similar results were obtained in shiitake studies ('WC380', 'WC377', and 'LE12'), where no influence of 60, 90, and 120 days of incubation was observed on mushroom diameter and mass(Royse & Bahler 1986). However, in studies with shiitake 'ICFC 510/03' for incubation periods of 30, 50, and 70 days, a 70-day incubation period resulted in larger mushroom diameter and mass(Alberti et al 2022), as observed for 'PSU 305' with incubation periods of 58 and 116 days, where the 116-day period yielded mushrooms with greater mass and diameter(Royse 1985).Previous reports indicate that the strain used may behave differently for both substrate and cultivation environment, and mushroom mass and size may be related to inherent genetic characteristics (Alice W. Chen 2005, Zied & Pardo-Giménez 2017), explaining the lack of influence of the incubation period on these variables in this experiment.In this study, a 70-day incubation period showed a smaller brown cap coverage area (63.54%) compared to a 110-day incubation period, which exhibited a brown cap coverage area of 92.17% (Figure2). Despite the smaller coverage, after removal from the cultivation bag and throughout the production period, the brown cap continued to develop, achieving complete block surface coverage.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Similar results were obtained in shiitake studies ('WC380', 'WC377', and 'LE12'), where no influence of 60, 90, and 120 days of incubation was observed on mushroom diameter and mass(Royse & Bahler 1986). However, in studies with shiitake 'ICFC 510/03' for incubation periods of 30, 50, and 70 days, a 70-day incubation period resulted in larger mushroom diameter and mass(Alberti et al 2022), as observed for 'PSU 305' with incubation periods of 58 and 116 days, where the 116-day period yielded mushrooms with greater mass and diameter(Royse 1985).Previous reports indicate that the strain used may behave differently for both substrate and cultivation environment, and mushroom mass and size may be related to inherent genetic characteristics (Alice W. Chen 2005, Zied & Pardo-Giménez 2017), explaining the lack of influence of the incubation period on these variables in this experiment.In this study, a 70-day incubation period showed a smaller brown cap coverage area (63.54%) compared to a 110-day incubation period, which exhibited a brown cap coverage area of 92.17% (Figure2). Despite the smaller coverage, after removal from the cultivation bag and throughout the production period, the brown cap continued to develop, achieving complete block surface coverage.…”
supporting
confidence: 83%
“…Parameters evaluated after the first flush, at 30 days for all incubation periods, included the earliness of production start (PS), calculated by the difference between the opening date and the production start; productivity (PR) calculated as a percentage of the final mushroom mass to axenic block fresh mass (1000g); biological efficiency (BE) calculated as a percentage of the final mushroom mass to axenic block after the production time; the number of mushrooms (NM) produced, and cap diameter (CD) (Alberti et al 2022). Additionally, cap brown formation area (ACM) was assessed on block opening day using ImageJ® software.…”
Section: Methodsmentioning
confidence: 99%
“…Shiitake naturally thrives in temperate climates and grows on dead trees by degrading cellulose, hemicellulose, and lignin (Chen et al, 2016). Although shiitake requires a longer incubation period than most mushrooms, including time for colonization, lumping, browning, and pinning (Alberti et al, 2022), it can be grown on several substrates, such as sawdust (Ashrafuzzaman et al, 2009), corncobs (Yu et al, 2022), and sunflower seed hulls (Curvetto et al, 2002). For centuries, shiitake has been cultivated on artificial substrates or logs under conditions similar to its natural habitat for commercial purposes in Japan, Korea, and China (Koo et al, 2016;Kwon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%